Using chimeric viruses to study Kaposi’s sarcoma-associated herpesvirus pathogenesis in mice - Kholod, Kateryna (2021)
The Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiological agent responsible for the development of sarcomas and other lymphoproliferative diseases. KSHV has the characteristic of establishing latent infections, persisting throughout the life of the host. Its host specificity limits the quantity of studies made in vivo but the discovery of MHV-68, a virus that naturally infects rodents and is genetically similar to the human γ-herpesvirus, allowed for the development of an animal model to study the mechanisms responsible for KSHV latent infection in vivo. The kLANA and mLANA proteins are structurally and functionally related. They are essential for the maintenance of latency and for the replication and segregation of the KSHV and MHV-68 viral episome. In several studies, the sequence immediately upstream of the internal repeat region in kLANA was described as being critical for viral episome replication in vitro. Therefore, to study the importance of this region for the viral DNA replication in a model of in vivo infection we generated 3 recombinant viruses: kLANAΔ306-320, kLANAΔ288-320 and kLANAΔ262-320, with different deletions in the referred region. These viruses were generated using a chimeric model in which the kLANA protein was cloned into the MHV-68 genome, replacing the original mLANA and allowing for the analysis of kLANA function in vivo. Our results showed that the recombinant viruses had similar latency levels as the kLANA virus, indicating that the deleted regions might not be responsible for viral DNA replication in vivo. In this study, we also studied if the mice genetic background, BALB/c or C57BL/6J, can affect the establishment of the viruses v-WT.yfp and v-kLANA.yfp latent infection in vivo. Our findings indicate that the mice strain BALB/c has higher frequency of latent infection than C57BL/6J, being the designated strain to use in further studies of KSHV in vivo.